Climate change and health: An analysis of causal relations on the spread of vector-borne diseases in Brazil. (10th March 2018) - Leal Filho, Walter; Bönecke, Juliane; Spielmann, Hannah; Azeiteiro, Ulisses M.; Alves, Fatima; Lopes de Carvalho, Mauren; Nagy, Gustavo J.
Abstract: The increases in greenhouse gas concentrations caused by anthropogenic activities such as industrial emissions, transport and burning of forests and other resources, recorded over the past decades, are known to have an impact on the global environment. In particular, this paper reviews the evidence that climate change has an impact on human health as a whole and on the spread of vector-borne diseases in particular. It offers an analysis of previous research on the connections between climate change and health, with a case study from Brazil, and lists some areas which may guide future policy-making. Highlights: Climate change can have significant impacts on health. Climate change contributes to the spread of vector-borne diseases. Developing countries such as Brazil are particularly vulnerable. Reliable policies are needed to address the problem.